AI Powered BI Systems Transforming Change Management and Strategic Decision Making in Enterprises - Ridhi Deora (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The incorporation of Advanced Intelligent Business Information Systems enhances change management and strategic decision making within the current day organization. These systems employ state-of-art technologies like machine learning, deep learning, and natural language processing and capture a large amount of data in order to deliver intelligent insights in support of swift, data-oriented, and foresighted decision making. Some key benefits are, Forecasting, what if analysis, real-time data dashboards and reports, real-time strategy with changing market trends; thus reducing the probabilities of wrong choices for an organisation’s strategic direction. In change management, AI BI systems help to identify areas of low productivity, workforce problems and other externalities in advance, thus making it possible to address them before they become problematic. The above systems help in addressing stakeholder communications and facilitating change by providing automated solutions, thus clearing out workloads of upcoming human resource challenges from human resource workers. They create an environment where adaptability and innovations are expected; they prepare enterprises for complicated environments where efficiency has to be achieved. This work aims to reveal the complex ways in which AI enhanced BI systems can support strategic acumen and sustainable business advancement. This is done through the presentation of applied research and examples of their potential for change, as well as outlining potential issues regarding their ethical application, their limitations, and how they can be used to adjust enterprise dynamics and sustain competitiveness in a globalized world.